Pengaruh Role Stress Terhadap Perilaku Burnout Auditor Yang Dimoderasi Oleh Emotional Quetient KAP Provinsi Bali - Rahayu, Luh Putu Devita; Widhiyani, Luh Sari (E-Jurnal Akuntansi; Vol 30 No 2 (2020), 2020)
The purpose of this study was to prove the influence of the role on auditor burnout and the influence of the role on auditor burnout which was moderated by emotional quetient (Case Study in KAP in Bali Province). This research was conducted at nine Bali Provincial Public Accountants Offices in 2018 with a total of 70 auditors as a sample with a saturated sample method. Data collection was done by interviews, as many as 11 were not used because they were not returned and 59 respondents who fulfilled the next criteria were treated with the analysis regression moderation analysis technique (MRA). Based on the results of the analysis, stress roles have a positive influence on auditor burnout behavior. Emotional quotient does not moderate or influence the positive influence of the role of stress on the influence of auditor burnout. Keywords: Role Stress; Emotional Quetient; Burnout Behavior.